2015
DOI: 10.1007/s10654-015-9998-4
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in conducting genome-wide association studies in highly admixed multi-ethnic populations: the Generation R Study

Abstract: Genome-wide association studies (GWAS) have been successful in identifying loci associated with a wide range of complex human traits and diseases. Up to now, the majority of GWAS have focused on European populations. However, the inclusion of other ethnic groups as well as admixed populations in GWAS studies is rapidly rising following the pressing need to extrapolate findings to non-European populations and to increase statistical power. In this paper, we describe the methodological steps surrounding genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 38 publications
0
107
1
Order By: Relevance
“…For genotyping, we used the infrastructure of the Human Genomics Facility (HuGe-F) of the Genetic Laboratory of the Department of Internal Medicine (www.glimdna.org). The GWAS dataset underwent a stringent QC process, which has been described in detail previously [5, 7, 84]. Most GWAS analyses are strongly embedded in the Early Growth Genetics (EGG) (http://egg-consortium.org/) and Early Genetics and Longitudinal Epidemiology (EAGLE) Consortia, in which several birth cohort studies combine their GWAS efforts focused on multiple outcomes in fetal life, childhood and adolescence.…”
Section: Genomics: Genetic Epigenetic and Microbiome Biobankmentioning
confidence: 99%
“…For genotyping, we used the infrastructure of the Human Genomics Facility (HuGe-F) of the Genetic Laboratory of the Department of Internal Medicine (www.glimdna.org). The GWAS dataset underwent a stringent QC process, which has been described in detail previously [5, 7, 84]. Most GWAS analyses are strongly embedded in the Early Growth Genetics (EGG) (http://egg-consortium.org/) and Early Genetics and Longitudinal Epidemiology (EAGLE) Consortia, in which several birth cohort studies combine their GWAS efforts focused on multiple outcomes in fetal life, childhood and adolescence.…”
Section: Genomics: Genetic Epigenetic and Microbiome Biobankmentioning
confidence: 99%
“…The Generation R Study is a multiethnic cohort. The largest subgroup is of Dutch/European origin (57%), with other ethnic groups including Turkish (7.4%), Surinamese (7.3%), and Moroccan (6.4%) (15). Our analyses were restricted to singleton live born children who had genomewide association data and at least one of the lipid measurements available.…”
Section: Design and Study Populationmentioning
confidence: 99%
“…SNPs were excluded if they had a minor allele frequency 0.001, a call rate <0.98, or if they were out of Hardy-Weinberg Equilibrium (P < 1E 6 ) (15). The genotyped dataset was then imputed to the 2.5 million SNPs of the HapMap II (release 22) cosmopolitan panel with MACH (version 1.0.15) software (14,15,17,18).…”
Section: Genetic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Studies assessing the contribution of variants to disease have shown that, in general, associated variants transcend ethnic groups, and play a role in disease susceptibility worldwide. There are analytical challenges to performing genome-wide association studies in the mixed ancestry and admixed populations, with care needed in both quality control and association testing, 9 but the benefits to genetic discovery from recruiting ancestrally heterogeneous populations are considerable. 10 The larger sample sizes attainable lead to novel loci being identified, 11 and differences in linkage disequilibrium patterns across populations open up the potential to identify causal variants at associated loci through using fine-mapping approaches.…”
Section: Use Of Multi-ethnic Groups In Genetic Researchmentioning
confidence: 99%